RELATIONSHIP BETWEEN SERUM SUBSTANCE P LEVELS AND ACNE VULGARIS - Putri Lubis, Ika Syani (Journal of Public Health Science, 2024)
This investigation aimed to see if serum substance P levels and acne vulgaris were related. This study applies the case-control method to an observational analytical investigation. Samples were collected at KSM Dermatology's Cosmetic Division Polyclinic. Blood samples were evaluated at the UI Faculty of Medicine, Integrated Laboratory, and venereology at UI Hospital, Medan. Each group in this study included a minimum of 18 samples. The study indicates a relationship between serum substance P levels and acne vulgaris. Acne vulgaris is 5.4 times more likely to occur in people with high serum substance P levels. greatest in males. The average serum substance P level in acne vulgaris is 62.6 ± 32.4 pg/ml, and the highest levels can be found in the age group of 28 to 32 years. The average serum substance P level of acne vulgaris based on gender is highest in men.